Use of Geothermal Energy to Degasification of Coal Beds - Vladimir B. Soloviov, Artem V. Leisle, Nina N. Smirnova (International Journal of Advanced Science and Technology, 2020)
In Russia and abroad, research and experimental work on the search for a rational technology for the complex extraction of coal and geothermal mineral resources are again being developed. A new wave of interest in this technology is conditioned by a number of reasons. The most important of these is fluctuation in oil prices (which in the past year have become more dependent on geopolitical attitude in a number of countries, including those in the OPEC countries) and natural gas, their limited resources, the growing scale of environmental damage from open or underground coal mining and its use in heat power plants. In addition, frequent changes in the hydrocarbon reserve indicators create either an obstacle or a "second breath" for national economies, but meanwhile economic indicators are even more closely tied to revenues from the extraction and sale of resources. The processing of extracted coal into more "pure" types of liquid or gaseous fuels could exclude only a part of the environmental damage, and in the economic sense could bring relative stability in the growth of the economy, as dependence on the sales of quoted resources will weaken and still requires a large expenditure. At the same time, the possibilities of increasing the efficiency of geothermal-coal technology and the complex physical and chemical processes taking place under these conditions have not been studied yet. The use of geothermal energy in combination with underground gasification or burning of substandard coal beds can reduce the cost of preparing a coolant for degassing the treated bed.